أثر تطبيق النموذج الياباني لإدارة الموارد البشرية على القيمة المضافة لأداء قطاع الصناعات التحويلية في مصر: دراسة ميدانية بالتطبيق على شركات صناعة الأدوية والكيماويات والمستلزمات الطبية - عبده، هاني محمد السعيد (جامعة عين شمس - كلية التجارة, 2020)
يهدف هذا البحث إلى تحديد معنوية الفروق بين آراء فئات مجتمع البحث حول أبعاد النموذج الياباني لإدارة الموارد البشرية وحول أبعاد القيمة المضافة لأداء قطاع الصناعات التحويلية في مصر، كما يهدف البحث بشكل أساسي إلى تحديد أثر تطبيق أبعاد النموذج الياباني لإدارة الموارد البشرية على القيمة المضافة لأداء قطاع الصناعات التحويلية، مع اختبار العلاقة ميدانياً بين المتغيرين في شركات صناعة الأدوية والكيماويات والمستلزمات الطبية في مصر. ويتمثل مجتمع البحث في أعضاء الإدارة العليا، ومديري الإدارات ورؤساء الأقسام، والعاملين بالشركات التابعة للشركة القابضة للأدوية والكيماويات والمستلزمات الطبية في مصر ، وقد اختار الباحث (٨) شركات منها كمجال للبحث والتطبيق من أصل (١١) شركة أي بنسبة ٧٢,٧٣% ، وقد بلغ عدد أعضاء الإدارة العليا بالشركات موضع الدراسة 31 مفردة ، وبالنسبة لفئة مديري الإدارات ورؤساء الأقسام بلغ عددهم ٦٧ مفردة ، أما بالنسبة لفئة العاملين فبلغ عددهم ١٦٥٢٨ مفردة ، وقد اعتمد الباحث على أسلوب الحصر الشامل بالنسبة لفئتي أعضاء الإدارة العليا ، ومديري الإدارات ورؤساء الأقسام ، أما بالنسبة لفئة العاملين فقد اعتمد الباحث على عينة عشوائية طبقية حجمها ٣٧٧ مفردة. وقد توصل الباحث إلى مجموعة من النتائج العامة للبحث ، من أهمها أن هناك تراجع في حجم الاستثمارات بالشركات موضع الدراسة ، وأن هذه الشركات تواجه مشكلات عديدة من أهمها ضعف التكنولوجيا المستخدمة في الإنتاج ، وعدم القدرة على تصنيع المادة الفعالة للدواء ، وضعف جهود البحوث والتطوير ، بالإضافة إلى الانخفاض الحاد في نسبة صادراتها من منتجات الأدوية إلى الواردات ، وقد توصل الباحث إلى أنه يوجد أثر معنوي إيجابي لتطبيق أبعاد النموذج الياباني لإدارة الموارد البشرية على القيمة المضافة لأداء الشركات موضع الدراسة ٠ وقد قدم الباحث في ختام بحثه مجموعة من التوصيات من أهمها ضرورة إجراء تقييم فنى شامل للشركات والمصانع العاملة في قطاع الصناعات التحويلية ، وإنشاء هيئة عليا مستقلة لصناعة الدواء في مصر ، وضرورة إصدار قانون التجارب السريرية، مع تعديل نظم تحليل واختبار عينات الأدوية والتي تتم بالمعامل المركزية لوزارة الصحة، ووضع استراتيجية متوازنة لتسعير الدواء المصري ، بالإضافة إلى إعداد رؤية استراتيجية شاملة للبحث العلمي والتطوير في قطاع صناعة الأدوية.
This research aims to determine the significance of differences between the views of research population categories on the dimensions of Japanese Human Resource Management Model and the dimensions of the added value of performance of manufacturing industries’ sector in Egypt. In addition, the research aims primarily to determine the effect of applying the dimensions of Japanese Human Resource Management Model on the added value of performance of manufacturing industries’ sector with testing the relationship between both variables in field in pharmaceutical, chemical and medical supplies companies in Egypt. The population of research consists of top management members, directors of administrations, heads of departments, and employees of companies affiliated to the Holding Company for Pharmaceutical, Chemical and Medical Supplies in Egypt. The researcher chose (8) companies out of 11 companies as a field of research and application, i.e. at a percentage of 72.73%. The number of top management members of companies under study was 31 individuals. For the category of directors of administrations and heads of departments, they were 67 individuals and for the category of employees, it consisted of 16528 individuals. The researcher used consensus method for both categories of top management members, and directors of administrations and heads of departments. For employee category, the researcher chose a random stratified sample consisting of 377 individuals. The researcher found a set of general findings of research and the most important of which are as follows: there is a decrease in investment volume in companies under study; these companies face several problems and the most important ones among these problems are the weakness of technology used in production, the inability to manufacture the active ingredient of drugs, the weak efforts of research and development, as well as the steep decline in their export to import ratio of pharmaceutical products. The researcher found that there is a significant and positive effect of applying the Japanese Human Resource Management Model on the added value of performance of companies under study. At the end of his research, the researcher presented a set of recommendations and the most important of which are as follows: it is necessary to perform an overall technical evaluation of companies and factories operating in manufacturing industries’ sector, and create an independent supreme authority for pharmaceutical industry in Egypt. In addition, it is necessary to enact the law of clinical trials with modifying the systems used for analyzing and testing drug samples in central laboratories of the Ministry of Health, develop a balanced strategy for pricing the Egyptian drugs, and prepare a comprehensive strategic vision of Scientific Research and Development in the sector of pharmaceutical industry.
Keywords: إدارة الموارد البشرية -- القيمة المضافة -- الصناعات التحويلية -- صناعة الأدوية -- مصر